Axis of success: Primary and secondary stability of implant - Nitin Sharma; Archana Nagpal; Anisha Kundal; Ayushi Singla; Vidushi Jindal (Wolters Kluwer Medknow Publications, 2021)
Primary and secondary stability mainly proceed along with mechanical phenomenon of implant engagement within the surrounding bone. Primary stability is an important element in attainment of secondary implant stability. Measuring stability of an implant helps dentist/operator about decision and timing of loading an implant. Primary and secondary implant stability is defined and discussed thoroughly. The factors affecting implant stability are classified and detailed in the simple manner in this review article. Till present time, no particular method has been established to evaluate the implant stability. Although resonance frequency analysis method evaluates stability of implants with the results outcome dependent on the sound theory, it surely cannot assure the success and failure or even long-term results of the dental implants.